Analytic Hierarchy Process Implementation As The Best Selection Of Study Program - Putra, Lakry Maltaf (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2015)
Developments in the world of IT is increasingly rapidly, is one of the triggers of the social development of the community in the form of a mindset that is logical and structured for fact and de jure. In the world of academia person must choose on the basis of ability, background and not loose all of the facts and de jure in determining decisions of the various forms of options considering the benefits in the present and future. If you do not select a result equally bad for the future of education a person who has participated in the academics to high level. Various assumptions verbally represented in the form of numerical order of facts and data can be calculated scientifically and unacceptable logic anyone. For it decision support System in selecting an option we can use the method of Analytical Hierarchy Process (AHP) assisted with the super decisions software.